Sedimentological Analysis Of Camocim Beach Zone, Ceará - Marques, Eduardo De Sousa; Claudino-Sales, Vanda C.; Pinheiro, Lidriana S. (Seven Editora, 2023)
The beaches represent dynamic environments and exchange of energy and matter between the continent and the ocean. The transport of sediments is constant and the features are constituted by unconsolidated materials, being characterized by maintaining fragile structures for the processes of human occupation. From granulometric analyzes performed according to preestablished protocols, it was possible to define the granulometric and chemical composition of the sands of the Barriers Beach and Lighthouse, in the city of Camocim, west coast of the State of Ceará. In the beach zone, subdivided into backshore, foreshore and nearshore, there are lithoctic sands, litobioclastic sands and bioclastic rocks, containing high concentrations of calcium carbonate from organic agents (shells, corals, algae etc.) and inorganic (from the ocean or continents), as well as the erosion of beach rocks. DOI: https://doi.org/10.56238/methofocusinterv1-098